Perioperative lidocaine infusions for the prevention of chronic postsurgical pain: a systematic review and meta-analysis of efficacy and safety. Issue 9 (September 2018) - Bailey, Martin; Corcoran, Tomas; Schug, Stephan; Toner, Andrew
Abstract : Abstract: Chronic postsurgical pain (CPSP) occurs in 12% of surgical populations and is a high priority for perioperative research. Systemic lidocaine may modulate several of the pathophysiological processes linked to CPSP. This systematic review aims to identify and synthesize the evidence linking lidocaine infusions and CPSP. The authors conducted a systematic literature search of the major medical databases from inception until October 2017. Trials that randomized adults without baseline pain to perioperative lidocaine infusion or placebo were included if they reported on CPSP. The primary outcome was the presence of procedure-related pain at 3 months or longer after surgery. The secondary outcomes of pain intensity, adverse safety events, and local anesthetic toxicity were also assessed. Six trials from 4 countries (n = 420) were identified. Chronic postsurgical pain incidence was consistent with existing epidemiological data. Perioperative lidocaine infusions significantly reduced the primary outcome (odds ratio, 0.29; 95% confidence interval, 0.18-0.48), although the difference in intensity of CPSP assessed by the short-form McGill Pain Questionnaire (4 trials) was not statistically significant (weighted mean difference, −1.55; 95% confidence interval, −3.16 to 0.06). Publication and other bias were highly apparent, as were limitations in trial design. Each study included a statement reporting no adverse events attributable to lidocaine, but systematic safety surveillance strategies were absent. Current limited clinical trial data and biological plausibility support lidocaine infusions use to reduce the development of CPSP without full assurances as to its safety. This hypothesis should be addressed in future definitive clinical trials with comprehensive safety assessment and reporting. Abstract : Supplemental Digital Content is Available in the Text.